A Versatile Multicomponent Assembly via β‐cyclodextrin Host–Guest Chemistry on Graphene for Biomedical Applications. Issue 3 (9th October 2012) - Dong, Haiqing; Li, Yongyong; Yu, Jinhai; Song, Yanyan; Cai, Xiaojun; Liu, Jiaqiang; Zhang, Jiaming; Ewing, Rodney C.; Shi, Donglu
Abstract A multi‐component nanosystem based on graphene and comprising individual cyclodextrins at its surface is assembled, creating hybrid structures enabling new and important functionalities: optical imaging, drug storage, and cell targeting for medical diagnosis and treatment. These nanohybrids are part of a universal system of interchangeable units, capable of mutilple functionalities. The surface components, made of individual β‐cyclodextrin molecules, are the "hosts" for functional units, which may be used as imaging agents, for anti‐cancer drug delivery, and as tumor‐specific ligands. Specifically, individual β‐cyclodextrin (β‐CD), with a known capability to host various molecules, is considered a module unit that is assembled onto graphene nanosheet (GNS). The cyclodextrin‐functionalized graphene nanosheet (GNS/β‐CD) enables "host–guest" chemistry between the nanohybrid and functional "payloads". The structure, composition, and morphology of the graphene nanosheet hybrid have been investigated. The nanohybrid, GNS/β‐CD, is highly dispersive in various physiological solutions, reflecting the high biostability of cyclodextrin. Regarding the host capability, the nanohybrid is fully capable of selectively accommodating various biological and functional agents in a controlled fashion, including the antivirus drug amantadine, fluorescent dye [5(6)‐carboxyfluorescein], and Arg‐Gly‐Asp (RGD) peptide‐targeting ligands assisted by an adamantine linker. The loading ratio of 5(6)‐carboxyfluorescein is as high as 110% with a drug concentration of 0.45 mg mL−1. The cyclic RGD‐functionalized nanohybrid exhibits remarkable targeting for HeLa cells.